Radial head arthroplasty with bipolar uncemented endoprothesis with metal – metal bearing - Boyko, Igor; Shcherbakov, Dmitriy; Makarov, Vasyl; Sabsay, Alexander; Maliy, Igor; Lazarenko, Gleb (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Objective: to review technical peculiarities of designed uncemented modular radial head endoprothesis and to analyze it clinical application in patients with fractures and dislocations of the radial head ІІІ–IV types by Mason-Hotchkiss. Methods: we studied clinical application of modular uncemented bipolar endoprothesis with metal-on metal bearing in 14 patients, age 43–74 years old. The follow-up was 6–24 months. Indications for arthroplasty were multifragments fractures and fractures with dislocation of ІІІ–IV types by Mason-Hotchkiss. Efficacy of treatment was assessed by Mayo Elbow Performance Score. Results: flexion in elbow joint in average was 130° (from 110° to 140°), average value of extension deficit — 3,2° (from 0° tо 10°), pronation — 77,86° (from 70° tо 90°), supination — 76,07° (from 80° tо 70°), flexion/extension — 127° (from 100° tо 140°), prosupination movements— 153° (from 140° tо 170°). We compared the volume of movements in elbow joint of operated site with contra lateral joint in 12 months of follow-up. Positive correlative connection of increased volume of movements was observed. The signs of elbow joint instability and significant complications during follow-up period were not find. According to Mayo Elbow Performance Score there were excellent results — 7 patients, good — 5, satisfactory result — 2, average score was 88,5. Conclusion: application of the new designed modular uncemented bipolar radial head endoprothesis allowed us to obtain positive results in term of 2 years of follow-up.